Sadaqah Financial Management and Accounting Practices in a Community - Niswatin; Nilawaty Yusuf; Ayu Rakhma Wuryandini; Amaliah, Tri Handayani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The present work delves into the financial management practice and accounting of sadaqah a association. It relied on an Islamic ethnomethodological approach. The research informants are the administrators and members of the association. The study found that the financial planning, collection, distribution and financial reporting of sadaqah was carried out simultaneously at night every 15th of the month of AD in different locations with a balance policy of less than two hundred and fifty thousand rupiah. Sadaqah collection is carried out in a closed booth and its distribution involves a minimum of two witnesses. study offers the need for the concept of social organizational financial accountability based on Islamic values. The research results also provide input for social organizations in the transparency of financial reporting.